2020
DOI: 10.3390/antiox9070616
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Protein Bound Methionine Sulfoxide by a Periplasmic Dimethyl Sulfoxide Reductase

Abstract: In proteins, methionine (Met) can be oxidized into Met sulfoxide (MetO). The ubiquitous methionine sulfoxide reductases (Msr) A and B are thiol-oxidoreductases reducing MetO. Reversible Met oxidation has a wide range of consequences, from protection against oxidative stress to fine-tuned regulation of protein functions. Bacteria distinguish themselves by the production of molybdenum-containing enzymes reducing MetO, such as the periplasmic MsrP which protects proteins during acute oxidative stress. The versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Nevertheless, DmsA was not demonstrated to reduce Met-O within proteins. Recently, the Rhodobacter sphaeroides periplasmic DMSO reductase DorA-type has been elegantly shown to reduce protein-bound S-Met-O ( Tarrago et al, 2020 ). In conclusion, MsrA, MsrB, MsrP, and DorA can reduce protein-bound Met-O residues and, per se , are involved in protein quality control processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, DmsA was not demonstrated to reduce Met-O within proteins. Recently, the Rhodobacter sphaeroides periplasmic DMSO reductase DorA-type has been elegantly shown to reduce protein-bound S-Met-O ( Tarrago et al, 2020 ). In conclusion, MsrA, MsrB, MsrP, and DorA can reduce protein-bound Met-O residues and, per se , are involved in protein quality control processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another enzyme, fRMsr (free methionine-(R)-sulfoxide reductase) specifically reduces the free form of Met-R-O [7][8][9]. Some bacteria also possess several molybdoenzymes that reduce exclusively the free MetO [10,11] or both the free and protein-bound MetO [12][13][14][15]. Despite the lack of sequence and structure similarities, MsrA, MsrB and fRMsr generally catalyze the reduction of MetO using a similar 3-steps-mechanism [9,16] : i) a 'catalytic' Cys (or, less frequently, a selenocysteine, Sec) reduces the target MetO and is converted into a sulfenic (or selenic) acid [17], ii) an internal 'resolving' Cys reduces it through the formation of an intramolecular disulfide bond, and finally iii) the oxidized Msr is regenerated through disulfide exchange with a thioredoxin [18].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction is reversible thanks to the action of methionine sulfoxide reductase (Msr) [12]. Four types of Msr have been identified that reduce Met(O) residues to their functional form [13]. The main types are the thiol-oxidoreductases MsrA and MsrB, which react specifically with diastereomers displaying the S-and R-configurations at the sulfur atom, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth type of Msr belongs to the dimethyl sulfoxide (DMSO) reductase family. One example is the periplasmic Rhodobacter sphaeroides DorA DMSO reductase, which reduces DMSO and both free and protein-bound Met-S-O [13]. The primary role of the first three types of Msr is to regulate the Met(O) level in proteins; they reduce Met(O) residues more efficiently in unfolded proteins than in folded proteins [17].…”
Section: Introductionmentioning
confidence: 99%